Development of a High Performance 1280×1024 InGaAs SWIR FPA Detector at Room Temperature - Zhang, Jia-Xin; Wang, Wei; Li, Zai-Bo; Ye, Hai-Feng; Huang, Run-Yu; Hou, Ze-Peng; Zeng, Hui; Zhu, Hong-xia; Liu, Chen; Yang, Xue-Yan; Shi, Yan-Li (Frontiers in Physics, 2021)
The 1280×1024 In0.53Ga0.47As short wave infrared (SWIR)focal plane arrays (FPAs) detector with planar-type back illuminated process have been fabricated. With indium bump flip chip bonding techniques, the InGaAs photodiode arrays (PDAs) were hybrid- integrated to the CMOS Readout Integrated Circuit (ROIC) with Correlated Double Sampling (CDS). The response spectral is 0.9μm-1.7μm. The test results show that the dark current density is 2.25nA/cm2 at 25℃, the detectivity D*is up to 1.1× 1013cm · Hz1 / 2 / W and the noise electron is as low as 48e- under CDS mode, the quantum efficiency (QE) is 88% at 1550nm, and the operability is more than 99.9%. Moreover, the dark current and noise electron have been studied theoretically in depth. The results indicate that the diffusion current is the main contribution of the dark current, and the ROIC noise electron is the main source of FPAs noise.